Efforts to Improve Product Quality and Marketing of Palm Sugar Through Branding and E-Catalog in Karang Bayan Village, Lingsar District, West Lombok Regency - Riyan Rifki Rivaldi; Sofianti Safitri; Devita Arianti; Farida Fasa; Imtiyaaz Yaasmiin; Komang Tri Ayu Widiantari; Wirawan Adi Pratama; Johanes Alexander Andry Sutanto; Lovina Rachmayani; Sri Andini Listiawati; Susilawati Susilawati (Unram Journal of Community Service, 2024)
The purpose of implementing this activity is to help improve the quality of palm sugar production in Karang Bayan Village and to be able to expand market share, both local and modern markets by marketing through social media. This study used a descriptive method, namely UNRAM KKN students in Karang Bayan Village, Lingsar District, West Lombok Regency for the 2023 period conducted a survey directly to the location of palm sugar production. Based on the results of the discussion, it can be concluded that the production process of solid palm sugar includes the preparation of tools and materials, the processing process which includes tapping, boiling, filtering, printing, as well as packaging and branding. Marketing is done through branding and e-catalogs. Branding is an effort to build and enhance the identity of a brand/brand with a very broad scope, while branding efforts include making a business name, logo and business location. While the E-catalog is data on various products that are designed with an editing application. E-catalog creation efforts include a list of business products as well as product information such as prices, product photos, cellphone numbers and addresses. The benefits of e-catalog itself are that it is easier to access by various parties, information on goods and services is more transparent and more effective in improving the performance of goods procurement